Moin Berta!: Ai chatterbot for practicing basic speaking in German language - Nur Syafiqa Natasha Mohd Paudzi (Tanjong Malim, 2023)
Moin Berta!: Ai chatterbot for practicing basic speaking in German language by Nur Syafiqa Natasha Mohd Paudzi